From Factories in the Field to Activist Scholar: Don Mitchell Reflects on Intellectual Practice and the State of the University Today. Issue 4 (2nd October 2018) - Gough, Anne; Valisena, Daniele
ABSTRACT: Don Mitchell is one of the most influential contemporary cultural geographers and has long been at the forefront of scholarship on intersections of capital, nature and labor. His work engages the geo-historical processes of landscape co-production and discusses how social, political and labor struggles that formed landscapes have been hidden or erased. Mitchell's research and work are informed by an urgency to uncover the forces shaping the human–land dialectic. It is difficult not to sense profound urgency at the current political–ecological conjuncture, which is why we turned to Don Mitchell to reflect on his research, intellectual practice and the state of academia and activism today. The first section of the interview centers on Mitchell's research and the tools and methods he employs in his work. In the second section of the interview, we discuss strategies and tactics in resistance struggles, campus activism and radical scholarship. Infused throughout the interview are the influences that have shaped Mitchell's unique approach to teaching, research and a critical academic life. We conclude with a section on current academic practice.